Implikasi Hukum Dari E-Commerce Dalam Perspektif Perlindungan Konsumen - Aris Priyadi; Teguh Anindito; Wiwin Muchtar Wiyono (Wijayakusuma Law Review, 2025)
This study aims to analyze the implications of the development of e-commerce for consumer protection in today's digital era. With the increase in online transactions, consumers face various challenges, including data security, fraud, and unclear product information. This study explores how consumer protection regulations and policies have been adapted to address these issues. The research method used is a literature review and descriptive analysis of regulations in force in several countries. The results indicate that although several countries have developed legal frameworks to protect consumers in e-commerce transactions, gaps remain that require further attention, particularly in law enforcement and consumer education. This study suggests the need for more comprehensive regulatory updates and effective education strategies to increase consumer awareness in the digital environment. Thus, the implications of e-commerce from a consumer protection perspective emphasize the importance of collaboration between the government, e-commerce service providers, and consumers to create a safe and transparent ecosystem.